PENCIPTAAN DESTINATION BRANDING KERATON KASUNANAN SOLO SEBAGAI UPAYA MENINGKATKAN MINAT KUNJUNGAN WISATAWAN DOMESTIK - Permana, Aan Ari; Fianto, Achmad Yanu Alif; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2016)
Abstract: Surakarta is known as a cultural heritage that has very diverse objects of historic legacy in the Middle East with the cultural diversity of the square as the influence of the phenomenon alkuturasi 3 Budaya.Timbulnya shift cultural values embodied in the philosophy that there is The square Hardiningrat. Because it takes a creation of a destination Branding Profile Books square Hardiningrat. To raise the cultural values such as the meaning, culture, philosophy and mythology contained in square Hardiningrat an effort to increase the interest of domestic tourists. Creation is based on the observation, interview and study the existing keyword menggunakansudut view the literature study, the aesthetic, social and cultural self-image and cultural products. By using the analytical method, which is supported by qualitative indicators STP and USP (Unique Selling Proposition) got "special trip to visit "as a design concept. "Luxury square Hidden In "as the title of a book by point of interest photographic illustrations, implemented on the creation of the work. To determine the effectiveness, feasibility and appropriateness of the work, the results of the test design with a Likert scale questionnaire with given on 111 respondents. Correlation analysis of the results of testing the design , it was found that all of the statements questionnaire correlated design testing , we found that all of the statements questionnaire has a significant correlation to be able to fulfill the purpose of the book with the loading of the statement , and the mean between 242-362 4 , 27- 4.62 Keywords: Creation, Destination Brandin, Square, Domestic Travelers